A survey among TB patients in Malabon, Metro Manila on knowledge, attitudes, beliefs, practices and experiences, health seeking behavior and compliance-related factors - Auer, Christian (1998)
This survey explores the characteristics of TB patients, their health seeking behavior, their perception of the health center staff, the case finding and case holding process (with emphasis on patient compliance; factors associated with non-compliance are established), the patients' beliefs as to the etiology of TB, and the emotional and social consequences of having TB.
Using a cross-sectional survery, 103 smear-positve TB patients who had been treated in one of the 23 health centers of Malabon were interviewed.
Eighty-five percent of the respondents mentioned cough, 59% fever and 37% hemoptysis as a symptom that caused them to go to a health facility. For 56% of the patients, a private doctor was the first health facility to be approached, and for 24%, it was a HC.
The patient delay (time span between time of onset of symptoms and going to a health facility) was more than eight weeks of only 22% of the patients. Men had a greater delay than women.
Regarding the intake of drugs, 69% stated that they had taken drugs daily. The others stated to at least once have forgotten to take their drugs. All patients were under self-administered treatment.
Thirty-eighty patients (37%) did not complete treatment (they dropped out of treatment). Only 7 of them dropped out of treatment within the first two months (and 12 dropped out after two to three months of treatment).
Only about one third of the respondents felt fully healed at the time of interview. Only 72% of the patients had not had TB before they fell sick with TB in 1996.
Multivariate analysis showed the following factors to be significantly associated with not completing treatment: (i)long waiting time in the health center; (ii)patient considers TB as really dangerous; (iii)patients has side effects; (iv)patient is 21 to 35 years old; (v) patient has small trusts in the drugs; (vi)patient feels much better within three months; (vii)patient perceived kindness of the HC staff as poor; and (viii) patient perceived sufficiency of the HC staff's explanations as low.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Tuberculosis; Tuberculosis -- Patients